Advanced glycation end-products are associated with diabetic neuropathy in young adults with type 1 diabetes - Al-Saoudi, Elaf; Christensen, Marie M. B.; Nawroth, Peter; Fleming, Thomas; Hommel, Eva E.; Jørgensen, Marit E.; Fleischer, Jesper; Hansen, Christian S. (Frontiers in Endocrinology, 2022)
Aims/hypothesis Advanced glycation end-products (AGEs) may contribute to the development of diabetic neuropathy. In young adults with type 1 diabetes, we aimed to investigate the association between AGEs and cardiovascular autonomic neuropathy (CAN) and distal symmetric polyneuropathy (DSPN). Methods This cross-sectional study comprised 151 young adults. CAN was assessed by cardiovascular autonomic reflex tests; lying-to-standing test, deep breathing test (E/I) and Valsalva manoeuvre, and by heart rate variability indices; the mean square of the sum of the squares of differences between consecutive R-R intervals and standard deviation of normal-to-normal intervals (SDNN), high (HF) and low frequency (LF) power, total frequency power and the LF/HF-ratio. DSPN was assessed by light touch, pain and vibration perception threshold (VPT), neuropathy questionnaires and objective measures. AGEs were analysed in four groups using z-scores adjusted for relevant confounders and multiple testing: i. “Glycolytic dysfunction”, ii. “Lipid peroxidation”, iii. “Oxidative stress” and iv. “Glucotoxicity”. Results A higher z-score of “glycolytic dysfunction” was associated with higher VPT (4.14% (95%CI 1.31;7.04), p = 0.004) and E/I (0.03% (95%CI 0.01;0.05), p = 0.005), “lipid peroxidation” was associated with higher LF/HF ratio (37.72% (95%CI 1.12;87.57), p = 0.044) and “glucotoxicity” was associated to lower SDNN (-4.20% (95%CI -8.1416; -0.0896), p = 0.047). No significance remained after adjusting for multiple testing. Conclusions/interpretations In young adults with type 1 diabetes, increased levels of AGEs involving different metabolic pathways were associated with several measures of CAN and DSPN suggesting that AGEs may play a diverse role in the pathogeneses of diabetic neuropathy.